Travelling in Italy during Turner's lifetime - Balzaretti, Ross; Piana, Pietro; Watkins, Charles (Tate, 2015)
The number of British travellers to Italy in search of health, education and increasingly leisure grew substantially during Turner’s lifetime. Like Turner, travellers recorded their observations in journals and diaries, and some turned their experiences into printed books and guidebooks. This essay examines this material and provides a vivid insight into the rich environment that shaped Turner’s artistic development.